Effect of deinstitutionalisation on quality of life for adults with intellectual disabilities: a systematic review - May, Peter; Mc Carron, Mary; O'Donovan, Mary-Ann; Normand, Charles; Murphy, Esther; Smith, Valerie (My University, 2019)
Objective: To review systematically the evidence on how deinstitutionalisation affects quality of life (QoL) for adults with intellectual disabilities. Design: Systematic review. Population: Adults (aged 18 years and over) with intellectual disabilities. Interventions: A move from residential to community setting. Primary and secondary outcome measures: Studies were eligible if evaluating effect on QoL or life quality, as defined by study authors. Search: We searched MEDLINE, PsycINFO, CENTRAL, CINAHL, EconLit, Embase and Scopus to September 2017 and supplemented this with grey literature searches. We assessed study quality using the Critical Appraisal Skills Programme suite of tools, excluding those judged to be of poor methodological quality. Results: Thirteen studies were included; eight quantitative studies, two qualitative, two mixed methods studies and one case study. There was substantial agreement across quantitative and qualitative studies that a move to community living was associated with improved QoL. QoL for people with any level of intellectual disabilities who move from any type of institutional setting to any type of community setting was increased at up to 1year postmove (standardised mean difference [SMD] 2.03; 95%CI [1.21 to 2.85], five studies, 246 participants) and beyond 1year postmove (SMD 2.34. 95%CI [0.49 to 4.20], three studies, 160 participants), with total QoL change scores higher at 24 months comparative to 12 months, regardless of QoL measure used. Conclusion Our systematic review demonstrated a consistent pattern that moving to the community was associated with improved QoL compared with the institution. It is recommended that gaps in the evidence base, for example, with regard to growing populations of older people with intellectual disability and complex needs are addressed.
PUBLISHED
Keywords: Deinstitutionalisation; Adults with intellectual disabilities; Community care - Adults with intellectual disabilities; Inclusive Society; INTELLECTUAL DISABILITY; Intellectual Disability; Home and community living; Social exclusion; Social participation; Social services, interventions and supports